Geospatial computing in mobile devices - Chen, Ruizhi; Guinness, Robert E. (Mobile communications series, 2014)
Geospatial computing includes utilizing computing devices and sensors to acquire, process, analyze, manage, and visualize geospatial data, which users can then interact with via a large variety of smart geospatial applications. This resource also covers various aspects of the application technologies, such as context detection and context intelligence.